2016
DOI: 10.1111/apt.13862
|View full text |Cite
|
Sign up to set email alerts
|

Addition of an immunomodulator can reverse antibody formation and loss of response in patients treated with adalimumab

Abstract: Summary Background Anti‐adalimumab antibodies (AAA) are associated with loss of clinical response (LOR). Addition of an immunomodulator has been shown to reverse immunogenicity and regain response with infliximab monotherapy. Similar data on adalimumab are lacking. Aim To study the impact of immunomodulator addition on the emergence of AAA and LOR among adalimumab therapy patients. Methods The databases of three tertiary medical centres were reviewed to identify patients who developed AAA during adalimumab mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 31 publications
(61 reference statements)
5
61
0
5
Order By: Relevance
“…Despite the questionable efficacy of CT when the anti-TNF is ADA, the same group has recently shown a similar result when adding IMM as salvage therapy to failing ADA in 23 patients (21 with CD, 2 with UC) with confirmed antibodies to ADA. Salvage therapy with IMM (14 with thiopurines, 9 with MTX) was associated with elimination of antibodies to ADA, increased ADA levels, and recapturing of response (median time to sero-reversal 5 mo) in 11 patients (48%)[26]. …”
Section: Is Ct Effective At All Stages Of Ibd Therapy?mentioning
confidence: 99%
“…Despite the questionable efficacy of CT when the anti-TNF is ADA, the same group has recently shown a similar result when adding IMM as salvage therapy to failing ADA in 23 patients (21 with CD, 2 with UC) with confirmed antibodies to ADA. Salvage therapy with IMM (14 with thiopurines, 9 with MTX) was associated with elimination of antibodies to ADA, increased ADA levels, and recapturing of response (median time to sero-reversal 5 mo) in 11 patients (48%)[26]. …”
Section: Is Ct Effective At All Stages Of Ibd Therapy?mentioning
confidence: 99%
“…They had confirmed antibodies on repeat measurements, and they underwent sero-reversal after the addition of a thiopurine or methotrexate, which resulted in a clinical response and normalization of biomarkers. 157 In unresponsive patients with therapeutic anti-TNF drug levels and undetectable ADAs, the inflammation may not be TNF mediated; hence, the patient may need to switch to a drug with an alternative mechanism of action. 151 Patients with therapeutic anti-TNF drug levels in the presence of detectable ADAs may have either transient ADAs or a false positive ADA test.…”
Section: Stopping or Reducing The Dose Of Anti-tnf Drugsmentioning
confidence: 99%
“…164 165 However, infliximab rescue therapy may be even less efficacious in hospital inpatients with more severe, steroid refractory disease, with 90 day colectomy rates reported as 29-60%. [155][156][157][158][159][160][161][162][163][164][165][166][167][168] A cohort study of 115 patients found that standard three dose infliximab induction was associated with lower rates of clinical response (70% v 41%; P=0.004), clinical remission (41% v 17%; P=0.015), and endoscopic remission (26% v 4%; P=0.046) in patients with severe ulcerative colitis than in those with only moderately severe disease. 155 Similarly, patients with severe ulcerative colitis who did not respond to infliximab induction had significantly more fecal loss of drug, 169 and lower day 14 trough levels 170 compared with infliximab responders.…”
Section: Skin Lesionsmentioning
confidence: 99%
“…Association with an immunomodulatory drug also seems to be a good option. Indeed, based on previous infliximab and adalimumab studies, we could consider that adding a concomitant immunosuppressive therapy for patients treated with golimumab monotherapy has a possible impact on antidrug antibody formation, and hence on a beneficial clinical outcome [31,32]. Moreover, it has been demonstrated in several clinical trials that the risk of serious adverse events with combination therapy is not greater than that with TNF antagonist monotherapy [33,34].…”
Section: Expert Opinionmentioning
confidence: 99%